Meteorological-Hydrological-Agricultural Drought Analysis of Devegeçidi Reservoir - Nermin Şarlak; Abdullah Muratoğlu; Şahnaz Tiğrek (Doğal Afetler ve Çevre Dergisi)
The Devegeçidi Dam was first opened in 1972 to irrigate 5800 hectares of land in the Diyarbakır region. The reservoir has been a feeding and breeding ground for migratory birds and some other living ecosystems for many years. However, from time to time, the water volume in the reservoir decreased to a level that could not meet the irrigation water demand and water had to be supplemented from other dams on the Tigris River. In this study, the reasons for the decrease of the water level in the Devegeçidi reservoir were analyzed in terms of meteorological, hydrological and agricultural use. For this purpose, the water resources feeding the dam and the characteristics of the irrigation area were taken into consideration. Within the framework of the study, the monthly operating data of the Devegeçidi Dam were analyzed using statistical methods. The monthly average reservoir volume, monthly total water inflow and monthly total water consumption data for the years 2008-2021 were first analyzed by Mann-Kendall trend analysis method and then by Locally Weighted Scatterplot Smoothing algorithm. Standard Precipitation Index (SPI), Palmer (PDSI) and self-calibrated Palmer (sc-PDSI) drought indices were applied to reveal the relationship between hydrological drought problem and precipitation data. Areas and yields of agricultural crops were analyzed using local TurkStat data and GIS-based CORINE land cover maps. Thus, the meteorological, hydrological and agricultural causes of the drought and water shortage problems in the reservoir were revealed.